American Mermaid - Langbein, Julia (Art historian) (New York : Doubleday, 2023)
"Penelope Schleeman, a consistently broke Connecticut high school teacher, is as surprised as anyone when her sensitive debut novel, 'American Mermaid'--the story of a wheelchair-bound scientist named Sylvia who discovers that her withered legs are the vestiges of a powerful tail--becomes a bestseller. Penelope soon finds herself lured to LA by promises of easy money to co-write the 'American Mermaid' screenplay for a major studio with a pair of male hacks. As the studio pressures Penelope to change 'American Mermaid' from the story of a fierce, androgynous eco-warrior to a teen sex object in a clam bra, strange things start to happen"--
Keywords: Authors -- Fiction; Mermaids -- Fiction; Adult fiction